2021
DOI: 10.1002/mas.21743
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights about albumin in cardiovascular diseases: Focus on heart failure

Abstract: The Human Plasma Proteome has always been the most investigated compartment in proteomics-based biomarker discovery, and is considered the largest and deepest version of the human proteome, reflecting the state of the body in health and disease.Even if efforts have been always dedicated to the refinement of proteomic approaches to investigate more deeply the plasma proteome, it should not be forgotten that also highly abundant plasma proteins, like human serum albumin (HSA), often neglected in these studies, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…35 Serum albumin levels have been reported to be inversely associated with the cardiovascular disease risk and aging, supporting its possible causal relationships with the oxidative stress-related status and diseases. [36][37][38] The mechanisms underlying the close associations of serum bilirubin and albumin levels with the progression to ESKD should be clari ed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…35 Serum albumin levels have been reported to be inversely associated with the cardiovascular disease risk and aging, supporting its possible causal relationships with the oxidative stress-related status and diseases. [36][37][38] The mechanisms underlying the close associations of serum bilirubin and albumin levels with the progression to ESKD should be clari ed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various genes such as PDK4 [140], ALB (albumin) [141], EGR1 [142], RYR3 [48], CYP27B1 [143], GATA6 [144], NR4A3 [145], TET2 [146], CACNA1D [147], KLF15 [148], CYP4A11 [149], ATOH8 [150], ATF3 [151], EGF (epidermal growth factor) [152], LPL (lipoprotein lipase) [153], PPARGC1A [154], PLG (plasminogen) [155], USP2 [156], PDE4D [157], RGS2 [158], ILK (integrin linked kinase) [159], SLC26A4 [160], PER1 [161], LGR4 [72], GABRB3 [162], TRPC1 [163], KL (klotho) [164], NOX4 [165], S100A12 [166], NEDD9 [167], ANKRD36 [168], IRF9 [169], GIMAP5 [170], ND2 [171], CHGA (chromogranin A) [172], DBH (dopamine beta-hydroxylase) [173], LTA (lymphotoxin alpha) [174], MPO (myeloperoxidase) [175], CD70 [176], LCN2 [177], TLR6 [178], TREM2 [179], NLRP12 [180], CCR5 [181], IL1RN [182], CX3CR1 [183], TRPM2 [184], TNF (tumor necrosis factor) [185], TLR7 [186], NOD2 [187], TNFRSF1B [188], CCR2 [181], CCL5 [189], PLA2G7 [190], TH (tyrosine hydroxylase) [191], WNT7A [192], ADRB3 [193], IL10RA [194], NOS3 [195], PIK3R5 [196], APLNR (apelin receptor) [197], COMP (cartilage oligomeric matrix protein) [198], RETN (resistin) [199], S100B [200], IGFBP1 [201] and COL1A1 [202] are crucial in the progression of hypertension. Evidence suggests that PDK4 [203], ALB (albumin) [204], EGR1 [205], RYR3 [206], DUSP1 [207], EYA4 [208], CYP27B1 [143<...…”
Section: Discussionmentioning
confidence: 99%
“…16,17) Serum albumin is often involved in the anti-inflammatory, antioxidant, and anticoagulant processes in the acute phase of the body and is associated with the incidence of long-term adverse cardiovascular events. 18) It has been demonstrated that GNRI is a better predictor of poor prognosis in patients with heart failure than any other model comparing BMI, serum albumin, and GNRI. 19) In a study of 213 elderly heart failure patients aged "80 years, mortality was found to be significantly higher in the low GNRI group than in the normal GNRI group and was significantly associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%